Frederick Douglass : Freedom's Voice, 1818-1845 - Lampe, Gregory P. (Book collections on Project MUSE., 1998)
This work in the MSU Press Rhetoric and Public Affairs Series chronicles Frederick Douglass's preparation for a career in oratory, his emergence as an abolitionist lecturer in 1841, and his development and activities as a public speaker and reformer from 1841 to 1845. Lampe's meticulous scholarship overturns much of the conventional wisdom about this phase of Douglass's life and career uncovering new information about his experiences as a slave and as a fugitive; it provokes a deeper and richer understanding of this renowned orator's emergence as an important voice in the crusade to.